Toll-like receptor 4-related immunostimulatory polysaccharides: Primary structure, activity relationships, and possible interaction models. (20th September 2016) - Zhang, Xiaorui; Qi, Chunhui; Guo, Yan; Zhou, Wenxia; Zhang, Yongxiang
Highlights: We summarize the monosaccharide type of different origin polysaccharides related to TLR4, including high plant origin polysaccharides et al. We briefly describe the glucosidic bond types of TLR4 related heteroglycans and homoglycans. The TLR4 related polysaccharides molecular weight ranges are summarized. The primary structures and activity relationships of polysaccharides with TLR4/MD-2 are also discussed. We speculate the possible interaction models of polysaccharide ligands with TLR4/MD-2. Abstract: Toll-like receptor (TLR) 4 is an important polysaccharide receptor; however, the relationships between the structures and biological activities of TLR4 and polysaccharides remain unknown. Many recent findings have revealed the primary structure of TLR4/MD-2-related polysaccharides, and several three-dimensional structure models of polysaccharide-binding proteins have been reported; and these models provide insights into the mechanisms through which polysaccharides interact with TLR4. In this review, we first discuss the origins of polysaccharides related to TLR4, including polysaccharides from higher plants, fungi, bacteria, algae, and animals. We then briefly describe the glucosidic bond types of TLR4-related heteroglycans and homoglycans and describe the typical molecular weights of TLR4-related polysaccharides. The primary structures and activity relationships of polysaccharides with TLR4/MD-2 are also discussed. Finally, based on the existing interaction models of LPS with TLR4/MD-2 and linear polysaccharides with proteins, we provide insights into the possible interaction models of polysaccharide ligands with TLR4/MD-2. To our knowledge, this review is the first to summarize the primary structures and activity relationships of TLR4-related polysaccharides and the possible mechanisms of interaction for TLR4 and TLR4-related polysaccharides.